Biochemical, biological and molecular characterization of an L-Amino acid oxidase (LAAO) purified from Bothrops pictus Peruvian snake venom - Lazo F. (2017)
We thank Prof. J.A. Eble, from the Institute for Physiological Chemistry and Pathobiochemistry, University of Münster, Germany for critical reading the manuscript. This work was supported by Convenio de Cooperación Bilateral CONCYTEC (Perú) - CNPq (Brazil), Grant 490269/2013-3 , Fundação de Amparo a Pesquisa do Estado de Minas Gerais (FAPEMIG, Brazil) and Programa Nacional de Innovación para la Competitividad y Productividad - Innóvate Perú (Contrato N° 131-FINCyT-IB-2013 ). This report is part of a dissertation for Doctoral Degree of Fanny Lazo to Post Graduate School in Biological Sciences, UNMSM.